1999
DOI: 10.1063/1.369729
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport properties of n-doped and p-doped Bi0.91Sb0.09 alloy thin films

Abstract: Articles you may be interested inEnhanced thermopower and thermoelectric performance through energy filtering of carriers in (Bi2Te3)0.2(Sb2Te3)0.8 bulk alloy embedded with amorphous SiO2 nanoparticles Study of structural-, compositional-, and thickness-dependent thermoelectric and electrical properties of Bi 93 Sb 7 alloy thin films In order to understand the doping behavior of extremely narrow band gap materials and to optimize their characteristics for use in a thermoelectric module, we performed n-and p-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 23 publications
(29 reference statements)
0
26
0
Order By: Relevance
“…[7][8][9] The Bi-Sb alloy shows excellent thermoelectric characteristics below 200 K. It is also apparent that the electronic transport properties depend strongly on the addition of impurities. [10][11][12][13] It is noteworthy that the thermoelectric efficiency of this material is enhanced greatly by the application of a magnetic field. 2,14,15 The dimensionless figure of merit reaches ZT % 1.1 under a 0.3 T magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The Bi-Sb alloy shows excellent thermoelectric characteristics below 200 K. It is also apparent that the electronic transport properties depend strongly on the addition of impurities. [10][11][12][13] It is noteworthy that the thermoelectric efficiency of this material is enhanced greatly by the application of a magnetic field. 2,14,15 The dimensionless figure of merit reaches ZT % 1.1 under a 0.3 T magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The distance between two layers within the bilayer is 1.60Å, while the distance between two bilayers is 2.26Å. We notice that the lattice parameters of the stable Bi-Sb compound at 50 at.% obey Vegard's law, as shown in Table IV. Our calculations were not able to reproduce the small band gap experimentally found for the composition range 0.07 < x < 0.22 [54]. In fact all investigated structures (ordered and disordered), apart from the ordered structure at 50 at.%, were found to be semimetallic.…”
Section: B Binary System Bi-sbmentioning
confidence: 52%
“…They are in general semimetallic with the exception of the range 0.07 < x < 0.22 where they are semiconducting with a narrow band gap. The maximum band gap is approximately 20 meV and is reached for x ∼ 0.15 [54]. In this section, we investigate the stability of layered structures at T = 0 K. In analogy with the previous binary systems, the occupation variable accounts for the fact that Bi or Sb belongs to an odd or even number of layers (irrespective of whether this is a Bi or Sb layer).…”
Section: B Binary System Bi-sbmentioning
confidence: 99%
“…For a pure metal, the diffusion thermoelectric power is ˛ = 2 k B 2 T/(eE F ) at temperatures where electron-phonon scattering is dominant [25,31]. Even though the above expression for thermoelectric power holds good for metals, we can approximately calculate the Fermi energy using this equation for degenerate regime of the doped Bi-Sb alloys since they are degenerate narrow band gap semiconductors.…”
Section: Electrical Conductivity and Seebeck Coefficientmentioning
confidence: 97%
“…For example, it was reported that Bi-Sb alloys with Z value of 1.79 × 10 −3 K −1 at 196 K was obtained through partial substitution of Nb for Sb [23]. Bulk Bi 100−x Sb x exhibits an n-type semiconductor behavior when 7 < x < 22 or a semimetal character when x ≤ 7 and x ≥ 22 [24,25]. At present, for cooling below room temperature, Bi-Sb alloys have been used in the n-type legs, coupled with p-type legs of (Bi,Sb) 2 (Te,Se) 3 [26,27].…”
Section: Introductionmentioning
confidence: 98%